2017
DOI: 10.1097/qad.0000000000001602
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical herpesvirus shedding among HIV-1-infected men on antiretroviral therapy

Abstract: Design We evaluated the subclinical shedding of 6 different herpesviruses in antiretroviral drug-treated HIV(+) men who have sex with men (MSM), and determined how this is associated with markers of inflammation and immune activation. Methods We obtained blood, semen, throat washing, urine, and stool from 15 antiretroviral-treated HIV-1-infected MSM with CD4+ T cell reconstitution, and 12 age-matched HIV(−) MSM from the Multicenter AIDS Cohort Study at 4 timepoints over 24 weeks to measure DNA levels of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…Even in healthy individuals, EBV periodically reactivates in the body which could stimulate local immune activation, potentially enhancing HIV replication (5). Studies in PLWH have attempted to evaluate associations between herpesvirus shedding (as determined by detectable virus in peripheral blood, throat washes, urine, stool, and/or semen) and HIV viral loads, however, given the high prevalence of other herpesviruses in PLWH, it is difficult to directly determine the effect of EBV on HIV replication and pathogenesis (25,26). Humanized mice could serve as a model to directly evaluate the effect of EBV infection on HIV replication, pathogenesis and latency in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Even in healthy individuals, EBV periodically reactivates in the body which could stimulate local immune activation, potentially enhancing HIV replication (5). Studies in PLWH have attempted to evaluate associations between herpesvirus shedding (as determined by detectable virus in peripheral blood, throat washes, urine, stool, and/or semen) and HIV viral loads, however, given the high prevalence of other herpesviruses in PLWH, it is difficult to directly determine the effect of EBV on HIV replication and pathogenesis (25,26). Humanized mice could serve as a model to directly evaluate the effect of EBV infection on HIV replication, pathogenesis and latency in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the physio-pathological explanation, the high frequency of shedding regardless of the virological response to ART could be related to the presence of immunoactivation, which was also demonstrated in patients with successful plasma HIV RNA suppression [35]. Agudelo Hernandez et al [36] reported that there was a trend of a positive correlation between the subclinical EBV DNA shedding rate (evaluated in different sites, included throat washings) and plasma levels of soluble CD14, which is a marker of monocyte activation, in HIV patients who have been virally suppressed on ART for a median of 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…EBV reactivation identified by PCR testing in plasma has also been documented in patients in intensive care units ( 20 , 21 ), in patients with COVID-19 (22-24), long COVID-19 ( 19 ), malaria ( 25 ) and HIV ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 90%